Effects of Sm2O3 and V2O5 Film Stacking on Switching Behaviors of Resistive Random Access Memories - Jian-Yang Lin; Kuang-Yao Wu; Kai-Huang Chen (Crystals, 2019)
In this work, the resistive switching characteristics of resistive random access memories (RRAMs) containing Sm2O3 and V2O5 films were investigated. All the RRAM structures made in this work showed stable resistive switching behavior. The High-Resistance State and Low-Resistance State of Resistive memory (RHRS/RLRS) ratio of the RRAM device containing a V2O5/Sm2O3 bilayer is one order of magnitude higher than that of the devices containing a single layer of V2O5 or Sm2O3. We also found that the stacking sequence of the Sm2O3 and V2O5 films in the bilayer structure can affect the switching features of the RRAM, causing them to exhibit both bipolar resistive switching (BRS) behavior and self-compliance behavior. The current conduction mechanisms of RRAM devices with different film structures were also discussed.